Different HLA associated gene combinations contribute to susceptibility for coeliac disease and dermatitis herpetiformis. Issue 5 (May 1986) - Sachs, J A; Awad, J; McCloskey, D; Navarrete, C; Festenstein, H; Elliot, E; Walker-Smith, J A; Griffiths, C E; Leonard, J N; Fry, L
Abstract : Forty two white patients of British or Irish descent with coeliac disease and 28 with dermatitis herpetiformis were typed for class I HLA-A, B, and C, and class II DR and DQ antigens. In coeliac disease there was a significant increase in the frequencies of A1, B8, DR3, DR7, and DQw2 compared with controls but no increase of DR2. In dermatitis herpetiformis there were similarly increased frequencies of A1, B8, DR3, and DQw2. In contrast with coeliac disease, however, the frequency of DR7 (18%) was no different from the control group but there was an increased frequency of DR2.